Thermally conductive siloxane composition for semiconductor encapsulation
Through the thermally conductive silicone composition of a specific composition, the problem of insufficient energy storage modulus in the prior art thermally conductive materials in semiconductor packaging is solved, and the thermal conductivity of heat is stable at high temperatures and the interface is reduced, so as to meet low hardness, Performance requirements for high elongation and high thixotropy.
Patent Information
- Application Number
- CN202310791373.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
In semiconductor packaging, existing thermally conductive materials are too high or too low in energy storage modulus, which leads to stress concentration or pumping out when the chip is warped, resulting in an increase in interface thermal resistance and cannot meet low hardness, high elongation, and high touch. Performance requirements for denaturation.
Using a specific composition of thermally conductive silicone composition, including organopolysiloxane A, B, C, D, E, catalyst F and inhibitor G, the wetting effect of thermally conductive powder is increased by regulating the viscosity and molar ratio and The bonding ability forms a material with excellent mechanical properties, which can resist substrate deformation and effectively transfer chip heat at high temperatures.
It is achieved to avoid pumping and peeling at high temperatures, reduce the interface thermal resistance, maintain long-term thermal conductivity, and has no significant impact after reliability tests of 150℃ and 1000h, and the thermal conductivity reaches 4W/m·K.
Smart Images

Figure CN119220100A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a thermally conductive silicone composition, in particular to a thermally conductive silicone composition for semiconductor packaging, and belongs to the technical field of organic silicon. Background Art
[0002] In the FC-BGA process, a nickel-plated aluminum alloy cover is used to protect the chip. However, the interface of the aluminum alloy cover and the chip cannot fully contact each other, and the air trapped in the invisible physical gap will reduce the heat conduction efficiency. For electronic components such as semiconductor chips, the heat generated during use will significantly reduce the chip power. In order to solve this problem, a thermally conductive organic siloxane composition with high thermal conductivity and excellent wetting effect is used between the cover and the chip as TIM1 material.
[0003] Due to the different CTE values of the substrate, cover plate and chip materials, warping and deformation will occur at different temperatures, causing different degrees of deformation at the corners and center of the chip; and because the deformation rate in different areas can reach up to 2000%, the TIM1 material will have different degrees of corner degradation, peeling or pumping problems, and the thermal resistance value will increase significantly; in addition, as the size of chips and substrates continues to increase, the deformation problem that the TIM1 material has to withstand will become more serious, and how to solve the degradation of the TIM1 material under high temperature conditions becomes particularly important.
[0004] Among existing thermal conductive materials, the storage modulus G' of silicone thermal conductive adhesive materials is too high, which cannot follow the warping caused by the heat of the chip, resulting in stress concentration and chip damage; while the storage modulus G' of silicone thermal conductive grease is too low, which is easy to be pumped out, and will become powdery after long-term use. Under current process conditions, the warping of the substrate causes the interface peeling of the TIM1 material and its own defects, resulting in a significant increase in the interface thermal resistance between the chip and the nickel-plated cover.
[0005] The prior art "CN103834352A two-component high thermal conductivity potting glue with excellent mechanical properties and preparation method thereof" aims to overcome the problem of reduced fluidity caused by using a large amount of general thermal conductive filler. It relates to thermal conductive potting glue and focuses on improving the fluidity of the siloxane composition. The hardness of the prepared material is in the shore A range and the thermal conductivity does not exceed 2W / m·K. Although it involves a polyalkoxyane composition, the raw materials used cannot meet the performance characteristics of low hardness, high elongation and high thixotropy that must be possessed by TIM1 materials used in the semiconductor packaging field. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, a thermally conductive silicone composition for semiconductor packaging is proposed. In this technical solution, the silicone composition has excellent mechanical and thermal conductivity, can resist the strain of the substrate at high temperature, avoid pumping out and peeling, and efficiently transfer the excess heat generated by the chip to the outside.
[0007] In order to achieve the above technical objectives, the following technical solutions are proposed: The thermally conductive silicone composition for semiconductor packaging includes the following components AG, which include, by mass, 40-60 parts of organopolysiloxane A, 10-30 parts of organopolysiloxane B, 600-1000 parts of thermally conductive powder C, 5-50 parts of organopolysiloxane D, 0.05-5 parts of organopolysiloxane E, 0.1-2 parts of catalyst F for catalyzing hydrosilylation reaction, and 0.1-2 parts of inhibitor G for catalyzing hydrosilylation reaction. Specifically: Component A: is an organopolysiloxane, each molecule contains at least two alkenyl groups that can participate in the hydrosilylation reaction, and does not contain silanol and siloxy groups. The terminal alkenyl group of component A is vinyl, allyl, pentenyl or hexenyl, preferably, the terminal alkenyl group is vinyl; the organic groups in the siloxane side chain of component A include alkyl, aryl and alkenyl groups, alkyl groups, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, etc.; aryl groups, such as phenyl, tolyl, etc.; alkenyl groups, such as vinyl, allyl, pentenyl, hexenyl, etc., preferably, the organic groups in the siloxane side chain are methyl; And, the viscosity of component A at 25°C is 10-10000 mPa·s. In order to better realize the present invention, component A with a viscosity of 300-5000 mPa·s is preferred. When the viscosity of component A is close to the lower limit, the present silicone composition can obtain extremely excellent flow properties; when the viscosity of component A is close to the upper limit, the present silicone composition can obtain better tensile strength and elongation at break. Therefore, considering comprehensively, component A with a viscosity of 300-5000 mPa·s is preferred; Component B: is an organic polysiloxane, each molecule contains at least two silicon hydrogen groups, and does not contain hydroxyl groups and alkoxy groups. The terminal group of component B is methyl, vinyl or hydrogen, preferably, the terminal group is methyl or hydrogen; the organic groups in the siloxane side chain of component B include alkyl, aryl and alkenyl groups, alkyl, alkyl, such as: methyl, ethyl, propyl, butyl, pentyl, hexyl, etc.; aryl, such as: phenyl, tolyl, etc.; alkenyl, such as: vinyl, allyl, pentenyl, hexenyl, etc., preferably, the organic group in the siloxane side chain is methyl; And, the viscosity of component B at 25°C is 3-300 mPa·s. In order to better realize the present invention, the viscosity of component B is preferably 10-200 mPa·s. When the viscosity of component B is close to the lower limit, the present silicone composition can obtain extremely excellent flow properties; when the viscosity of component B is close to the upper limit, the present silicone composition can obtain a higher hardness. Therefore, after comprehensive consideration, the viscosity of component B is preferably 10-100 mPa·s. Regarding the relationship between component A and component B: the molar ratio between the hydrogen group in component B and the vinyl group in component A is 0.3-5:1, and preferably, the molar ratio between the hydrogen group in component B and the vinyl group in component A is 0.5-3:1. When the content of component B is close to the lower limit, the present siloxane composition can obtain a soft physical state after curing; when the content of component B is close to the upper limit, the present siloxane composition can obtain a higher hardness after curing. Therefore, considering comprehensively, the molar ratio between the hydrogen group in component B and the vinyl group in component A is preferably 0.5-3:1; Component C: thermally conductive powder, a material with a relatively high thermal conductivity, including aluminum powder, copper powder, silver powder, nickel powder, nickel-plated silver powder, aluminum nitride powder, silicon nitride powder, diamond powder, graphene powder, aluminum oxide powder, zinc oxide powder, and white carbon black powder, etc. The shape of component C can be angular, spherical, spherical, rod-shaped, or other irregular shapes. In order to better realize the present invention, spherical or spherical shapes are preferred; And, the average particle size of component C is 0.1-120 μm. In order to better realize the present invention, component C with an average particle size of 0.1 to 60 μm is preferred. When the average particle size of component C is close to the lower limit, the thermal conductive powder will be difficult to disperse in the present siloxane composition; when the average particle size of component C is close to the upper limit, the surface of the present siloxane composition will be rough after curing; Component D: is an organopolysiloxane containing a hydrolyzable functional group, and its structural formula is shown in the following formula I: Formula I; In Formula I, the structural formula of X is shown in Formula II below: Formula II; In formula I or / and formula II, R1 is n-butyl, ethyl, propyl, isopropyl, sec-butyl, pentyl, hexyl or trimethylsilyl; R2 is methyl; R3 is methyl, phenyl or trifluoropropyl; R4 is methyl or phenyl; R5 is ethylene, propylene, hexyl, octyl, ethylenephenyl, 3-(methylpropionyloxy)propyl or 3-(propionyloxy)propyl; R6 is methyl, ethyl or isopropyl; In formula I, m=1-60, n=0-60, p=0-60, and are integers; Also, component D dehydrates and condenses with the hydroxyl groups on the surface of the thermally conductive powder (component C) at high temperature to form a stable silicon-oxygen bond, which eventually grafts long-chain alkanes or siloxane segments onto the surface of the thermally conductive powder, thereby increasing the wetting effect of the powder and the organopolysiloxane; Component E: is an organopolysiloxane containing epoxy groups and alkoxy groups, and its structural formula is shown in the following formula III or IV: Formula III; Formula IV; Wherein, in formula III, R7 is methyl, vinyl or hydrogen; R8 is methyl, n-butyl, ethyl, propyl, isopropyl, sec-butyl, pentyl, hexyl, hydrogen, vinyl or trimethylsilyl; In formula III or / and formula IV, m=1-120, n=1-120, x=1-120, and are integers; Furthermore, component E undergoes a ring-opening or hydrolysis reaction at high temperature, and dehydrates and condenses with the hydroxyl groups on the surface of nickel or single crystal silicon to form a stable silicon-oxygen bond, which ultimately enables the siloxane composition to have a certain strength of bonding ability; Component F: including chelates of chloroplatinic acid, such as alcohol-modified chloroplatinic acid, chloroplatinic acid hexahydrate, platinum chelates of olefins, platinum chelates of carbonyls, platinum chelates of alkenylsiloxanes, platinum chelates of alkynylsiloxanes, platinum chelates of organosilicon polysiloxanes, chelates of chloroplatinic acid and β-diketones, and chelates of chloroplatinic acid and 1,3-divinyltetramethyldisiloxane. In order to better realize the present invention, the catalyst is preferably a platinum chelate of alkenylsiloxane and / or a platinum chelate of alkynylsiloxane. Component G: an inhibitor of catalytic hydrosilylation reaction, that is, a substance that inhibits the catalytic activity of platinum, which can be selected according to needs, such as polyvinyl compounds, acetylenic compounds or nitrogen compounds.
[0008] The method for using a thermally conductive silicone composition for semiconductor packaging comprises: applying the thermally conductive silicone composition between a chip and a nickel-plated aluminum alloy cover plate, curing the composition at 125° C. for more than 2 hours to ensure that the composition has a corresponding storage modulus and adhesion, and then repeatedly performing a thermal shock test, and the result shows that it is difficult to pump out or peel off, thereby reducing the increase in interface thermal resistance.
[0009] The beneficial technical effects brought about by adopting this technical solution are: 1. In the present invention, the thermally conductive silicone composition has good mechanical properties and suitable modulus. After curing, it can fit the chip and the cover tightly and can efficiently transfer the heat generated by the chip to the shell. When the chip substrate is severely deformed and warped due to long-term heat, the composition will not produce significant interface peeling or cohesive failure. For example, after implementing a 150°C, 1000h reliability test, it will not significantly affect the thermal conductivity; 2. The present invention adopts polydimethylsiloxane with a specific segment structure, and controls the cross-linking structure of the siloxane composition by adjusting the ratio of silicon hydrogen to silicon vinyl groups and reducing the number of silicon hydrogen groups remaining in the system. Under long-term high temperature conditions, the hardness will not increase significantly; at the same time, it is found in the experiment that the elongation, storage modulus and loss modulus of the composition are within a specific range, and the prepared material can follow the deformation of the chip and the substrate without pumping out or internal tearing; by adding polysiloxane containing specific epoxy groups and alkoxy groups, the prepared material can form an effective bond with the chip and the substrate, and under long-term high temperature conditions, the contact surface will not detach or crack; by adding a high thermal conductivity powder filler and optimizing the compounding ratio, the siloxane composition can achieve a thermal conductivity of 4W / m·K at a lower filling amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is the SAT diagram of the chip after 150°C, 1000h reliability test. DETAILED DESCRIPTION
[0011] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0012] In the following examples, the thermal conductivity involved is tested at 65°C, and other properties are tested at 25°C; Modulus of the thermally conductive silicone composition: The modulus of the composition was measured using a rheometer (Anton Paar) using a 0° disc, a temperature of 125°C, and a shear frequency of 10 Hz; Thermal conductivity of thermally conductive silicone composition: Based on ASTM-D5470 Standard Test Method for Thermal Conductivity of Thermally Conductive Electrical Insulating Materials, the sample is a cylinder with a diameter of 30 mm and a height of 2 mm, and the thermal conductivity is tested at 40 N and 65 ° C; Hardness of the thermally conductive silicone composition: Based on the ASTM-D2240 rubber pocket durometer indentation hardness test method, the hardness of the sample is tested using a Shore 00 durometer; Elongation at break of the thermally conductive organosiloxane composition: based on GB / T 528-2009, determination method for tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, with a sample thickness of 2 mm.
[0013] Example 1 This embodiment provides a thermally conductive siloxane composition for semiconductor packaging, which comprises the following components in parts by mass: Organopolysiloxane A 50 parts Organopolysiloxane B 18.8 parts Thermal Conductive Powder C 700 copies Organopolysiloxane D 7 parts Organopolysiloxane E 0.05 parts Catalyst F for catalyzing hydrosilylation reaction 0.4 parts Inhibitor G for catalytic hydrosilylation reaction 0.1 part Among them, organopolysiloxane A: each molecule contains two alkenyl groups that can participate in the hydrosilylation reaction, and does not contain silanol and siloxy groups. The terminal alkenyl group is vinyl, and the organic group in the siloxane side chain is methyl; the viscosity at 25°C is 300mPa·s; Organopolysiloxane B: a mixture of multiple hydrogen-containing siloxanes, including a siloxane with a viscosity of 20 mPa·s, a methyl group capped at both ends of the molecular chain, and a hydrogen group and a methyl group in the side chain, and a siloxane with a viscosity of 100 mPa·s, a hydrogen group capped at both ends of the molecular chain, and a methyl group in the side chain; The molar ratio between the vinyl groups in the organopolysiloxane A and the hydrogen groups in the organopolysiloxane B was 1:0.87.
[0014] Thermal conductive powder C: a mixture of spherical aluminum powder and zinc oxide powder, with an average particle size of 10 μm; Organic polysiloxane D: contains a hydrolyzable functional group, and its structural formula is shown in the following formula I: Formula I; In Formula I, the structural formula of X is shown in Formula II below: Formula II; Wherein, in Formula I and Formula II, R1 is n-butyl, R2 is methyl, R3 is methyl, R4 is methyl, R5 is ethylene and R6 is methyl; And, in formula I, m=1, n=20, p=60; Organic polysiloxane E: contains epoxy groups and alkoxy groups, and its structural formula is shown in the following formula III or IV: Formula III; Formula IV; Wherein, in formula III, R7 is methyl, R8 is methyl; In formula III and formula IV, m=1, n=120, x=1; Catalyst F for catalyzing the hydrosilylation reaction: chloroplatinic acid hexahydrate; Inhibitor G for catalyzing hydrosilylation reaction: a polyvinyl compound.
[0015] The performance indexes of the thermally conductive silicone composition are shown in Table 1 below. After the reliability test at 150°C for 1000 hours, the chip SAT diagram is shown in Table 1 below. Figure 1 shown.
[0016] Example 2 This embodiment provides a thermally conductive siloxane composition for semiconductor packaging, which comprises the following components in parts by mass: Organopolysiloxane A 44 parts Organopolysiloxane B 21.4 parts Thermal Conductive Powder C 600 copies Organopolysiloxane D 14 parts Organopolysiloxane E 0.05 parts Catalyst F for catalyzing hydrosilylation reaction 0.67 parts Inhibitor G for catalytic hydrosilylation reaction 0.43 parts Among them, organopolysiloxane A: each molecule contains three alkenyl groups that can participate in the hydrosilylation reaction, and does not contain silanol and siloxy groups. The terminal alkenyl group is a hexenyl group, and the organic group in the siloxane side chain is a hexenyl group; the viscosity at 25°C is 3000mPa·s; Organopolysiloxane B: a mixture of multiple hydrogen-containing siloxanes, including a siloxane with a viscosity of 20 mPa·s, a methyl group capped at both ends of the molecular chain, and a hydrogen group and a methyl group in the side chain, and a siloxane with a viscosity of 100 mPa·s, a hydrogen group capped at both ends of the molecular chain, and a methyl group in the side chain, and a siloxane with a viscosity of 200 mPa·s, a hydrogen group capped at both ends of the molecular chain, and a methyl group in the side chain; The molar ratio between the vinyl groups in the organopolysiloxane A and the hydrogen groups in the organopolysiloxane B is 1:0.68, and the molar ratio between the vinyl groups in the organopolysiloxane A and the pendant hydrogen groups in the organopolysiloxane B is 1:0.55; Thermal conductive powder C: a mixture of spherical aluminum powder and zinc oxide powder, with an average particle size of 10 μm; Organic polysiloxane D: contains a hydrolyzable functional group, and its structural formula is shown in the following formula I: Formula I; In Formula I, the structural formula of X is shown in Formula II below: Formula II; Wherein, in Formula I and Formula II, R1 is isopropyl, R2 is methyl, R3 is trifluoropropyl, R4 is phenyl, R5 is octylene and R6 is ethyl, And, in formula I, m=60, n=0, p=1; Organic polysiloxane E: contains epoxy groups and alkoxy groups, and its structural formula is shown in the following formula III or IV: Formula III; Formula IV; Wherein, in formula III, R7 is a vinyl group, and R8 is a hydrogen group; In formula III and formula IV, m=120, n=1, x=120; Catalyst F for catalyzing the hydrosilylation reaction: a chelate of 1,3-divinyltetramethyldisiloxane; Inhibitor G for catalyzing hydrosilylation reaction: 2-methyl-3-butynyl-2-ol.
[0017] Among them, the performance indicators of the thermally conductive silicone composition are shown in Table 2.
[0018] Example 3 This embodiment provides a thermally conductive siloxane composition for semiconductor packaging, which comprises the following components in parts by mass: Organopolysiloxane A 45 parts Organopolysiloxane B 24 parts Thermal Conductive Powder C 900 copies Organopolysiloxane D 45 parts Organopolysiloxane E 1.5 parts Catalyst F for catalyzing hydrosilylation reaction 1 part 2 parts of inhibitor G for catalytic hydrosilylation reaction Among them, organopolysiloxane A: each molecule contains four alkenyl groups that can participate in the hydrosilylation reaction, and does not contain silanol and siloxy groups. The terminal alkenyl group is pentenyl, and the organic group in the siloxane side chain is phenyl; the viscosity at 25°C is 500mPa·s; Organopolysiloxane B: a mixture of multiple hydrogen-containing siloxanes, including a siloxane with a viscosity of 20 mPa·s, a methyl group capped at both ends of the molecular chain, and a hydrogen group and a methyl group in the side chain, and a siloxane with a viscosity of 100 mPa·s, a hydrogen group capped at both ends of the molecular chain, and a methyl group in the side chain, and a siloxane with a viscosity of 200 mPa·s, a hydrogen group capped at both ends of the molecular chain, and a methyl group in the side chain; The molar ratio between the vinyl groups in the organopolysiloxane A and the terminal hydrogen groups in the organopolysiloxane B is 1:0.78, and the molar ratio between the vinyl groups in the organopolysiloxane A and the pendant hydrogen groups in the organopolysiloxane B is 1:0.35; Thermal conductive powder C: a mixture of spherical aluminum powder and zinc oxide powder, with an average particle size of 10 μm; Organic polysiloxane D: contains a hydrolyzable functional group, and its structural formula is shown in the following formula I: Formula I; In Formula I, the structural formula of X is shown in Formula II below: Formula II; Wherein, in formula I and formula II, R1 is pentyl, R2 is methyl, R3 is methyltrifluoropropyl, R4 is methyl, R5 is 3-(propionyloxy)propyl, R6 is ethyl, And, in formula I, m=20, n=10, p=5, and are integers; Organic polysiloxane E: contains epoxy groups and alkoxy groups, and its structural formula is shown in the following formula III or IV: Formula III; Formula IV; Wherein, in formula III, R7 is a hydrogen group, and R8 is a sec-butyl group; In formula III and formula IV, m=100, n=60, x=5, and are integers; Catalyst F for catalyzing the hydrosilylation reaction: a platinum chelate of an alkynyl siloxane; Inhibitor G for catalyzing the hydrosilylation reaction: 3,5-dimethyl-1-hexynyl-3-ol.
[0019] The performance indicators of the thermally conductive silicone composition are shown in Table 3.
[0020] Examples 4-7 and Comparative Examples 1-4 This embodiment provides a variety of thermally conductive silicone compositions, which are as follows: The organopolysiloxane A used is polydimethylsiloxane, the two ends of the molecular chain are capped by a vinyl group, and the viscosity is 300 mPa·s; The organopolysiloxane B-1 used is a siloxane containing methyl groups in the side chain, with both ends of the molecular chain capped by hydrogen groups, a viscosity of 100 mPa·s, and a hydrogen group content of 0.025%; The organopolysiloxane B-2 used is a siloxane containing hydrogen and methyl groups in the side chain, with both ends of the molecular chain capped by methyl groups, a viscosity of 20 mPa·s, and a hydrogen content of 0.14%; The organopolysiloxane B-3 used is a siloxane containing hydrogen and methyl groups in the side chain, with both ends of the molecular chain capped by methyl groups, a viscosity of 75 mPa·s, and a hydrogen content of 0.24%; The organopolysiloxane B-4 used is a siloxane containing hydrogen and methyl groups in the side chain, with both ends of the molecular chain capped by methyl groups, a viscosity of 65 mPa·s, and a hydrogen content of 0.2%; The thermally conductive powder C-1 used was aluminum powder with an average particle size of 20 μm after being treated with organopolysiloxane D; The thermally conductive powder C-2 used was aluminum powder with an average particle size of 1 μm after being treated with organopolysiloxane D; The thermally conductive powder C-3 used is zinc oxide powder with an average particle size of 1 μm after being treated with organopolysiloxane D; The structure of the organopolysiloxane E (tackifier) used is shown in Formula III; The catalyst F used is an isopropanol solution of chloroplatinic acid; The catalyst G used is a mixture of dimethylbutynol and toluene; The above components A, B-1, B-2, C-1, C-2, C-3, E, F and G were mixed according to the amounts shown in Table 4-5 and the following preparation method to prepare the corresponding thermally conductive silicone composition; in addition, control examples (Comparative Examples 1-4) of this embodiment were set according to the amounts shown in Table 4-5 and the following method.
[0021] The preparation method includes: dispersing A, B-1, B-2, C-1, C-2, C-3, E and G in a SpeedMixer high-speed mixer at a rotation speed of 2000RPM for 120s; cooling it to room temperature, adding a catalyst F for catalyzing the hydrosilylation reaction, and dispersing it in a SpeedMixer high-speed mixer at a rotation speed of 1000RPM for 120s to obtain the corresponding thermally conductive silicone composition.
[0022] The results of the thermally conductive silicone compositions are shown in Tables 4-5 below.
[0023] From the above, it can be seen that when the modulus of the thermally conductive silicone composition is too low, the gel layer will have obvious pumping or fault problems after the chip is subjected to high temperature treatment of 260°C reflow soldering. At the same time, the selection of side chain hydrogen-containing siloxane will also affect the thermal stability of the composition.
[0024] After the thermally conductive silicone composition forms an effective bond with nickel, there is no obvious peeling or falling off at the thermal conductive interface after the chip is aged for a long time at 150°C. On the contrary, in the comparison sample without bonding, an obvious air layer appears at the thermal conductive interface, which greatly increases the thermal resistance and reduces the heat transfer efficiency.
[0025] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A thermally conductive silicone composition for semiconductor packaging, characterized in that: In parts by mass, it includes the following components: Organopolysiloxane A 40-60 parts Organopolysiloxane B 10-30 parts Thermal Conductive Powder C 600-1000 copies Organopolysiloxane D 5-50 parts Organopolysiloxane E 0.05-5 parts Catalyst F for catalyzing hydrosilylation reaction 0.1-2 parts Inhibitor G for catalytic hydrosilylation reaction 0.1-2 parts Wherein, the organopolysiloxane A contains at least two alkenyl groups that can participate in the hydrosilylation reaction in each molecule, and does not contain silanol groups and silanoxy groups; Organopolysiloxane B: contains at least two silicon hydrogen groups in each molecule, and does not contain hydroxyl groups and alkoxy groups; Organopolysiloxane D: contains hydrolyzable functional groups; Organopolysiloxane E: contains epoxy groups and alkoxy groups; The molar ratio between the vinyl groups in the organopolysiloxane A and the hydrogen groups in the organopolysiloxane B is 1:0.5-3.
2. The thermally conductive silicone composition for semiconductor packaging according to claim 1, characterized in that: In the organopolysiloxane A, the terminal alkenyl group is vinyl, allyl, pentenyl or hexenyl, and the organic group in the siloxane side chain includes methyl, ethyl, propyl, butyl, pentyl, hexyl, phenyl, tolyl, vinyl, allyl, pentenyl or hexenyl.
3. The thermally conductive silicone composition for semiconductor packaging according to claim 2, characterized in that: The viscosity of the organopolysiloxane A at 25° C. is 300-5000 mPa·s.
4. The thermally conductive silicone composition for semiconductor packaging according to claim 1, characterized in that: In the organopolysiloxane B, the terminal group is a methyl group, a vinyl group or a hydrogen group, and the organic group in the siloxane side chain includes a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a phenyl group, a tolyl group, a vinyl group, an allyl group, a pentenyl group or a hexenyl group.
5. The thermally conductive silicone composition for semiconductor packaging according to claim 4, characterized in that: The viscosity of the organopolysiloxane B at 25° C. is 10-200 mPa·s.
6. The thermally conductive silicone composition for semiconductor packaging according to claim 1, characterized in that: The thermally conductive powder C includes aluminum powder, copper powder, silver powder, nickel powder, nickel-plated silver powder, aluminum nitride powder, silicon nitride powder, diamond powder, graphene powder, aluminum oxide powder, zinc oxide powder or white carbon black powder; the thermally conductive powder C is spherical or quasi-spherical, with an average particle size of 0.1-60 μm.
7. The thermally conductive silicone composition for semiconductor packaging according to claim 1, characterized in that: The structural formula of the organopolysiloxane D is shown in the following formula I: Formula I; In Formula I, the structural formula of X is shown in Formula II below: Formula II; Wherein, in formula I or / and formula II, R1 is n-butyl, ethyl, propyl, isopropyl, sec-butyl, pentyl, hexyl or trimethylsilyl; R2 is methyl; R3 is methyl, phenyl or trifluoropropyl; R4 is methyl or phenyl; R5 is ethylene, propylene, hexyl, octyl, ethylenephenyl, 3-(methylpropionyloxy)propyl or 3-(propionyloxy)propyl; R6 is methyl, ethyl or isopropyl; And, in Formula I, m=1-60, n=0-60, p=0-60, and are integers.
8. The thermally conductive silicone composition for semiconductor packaging according to claim 1, characterized in that: The structural formula of the organopolysiloxane E is shown in the following formula III or IV: Formula III; Formula IV; Wherein, in formula III, R7 is methyl, vinyl or hydrogen; R8 is methyl, n-butyl, ethyl, propyl, isopropyl, sec-butyl, pentyl, hexyl, hydrogen, vinyl or trimethylsilyl; In formula III or / and formula IV, m=1-120, n=1-120, x=1-120, and are integers.
9. The thermally conductive silicone composition for semiconductor packaging according to claim 1, characterized in that: The catalyst F for catalyzing the hydrosilylation reaction is alcohol-modified chloroplatinic acid, chloroplatinic acid hexahydrate, platinum chelates of olefins, platinum chelates of carbonyls, platinum chelates of alkenylsiloxanes, platinum chelates of alkynylsiloxanes, platinum chelates of organosilicon polysiloxanes, chelates of chloroplatinic acid and β-diketone, and chelates of chloroplatinic acid or 1,3-divinyltetramethyldisiloxane; The inhibitor G for catalyzing the hydrosilylation reaction is a polyvinyl compound, an acetylenic compound or a nitrogen compound.
10. The thermally conductive silicone composition for semiconductor packaging according to claim 1, characterized in that: The method for using the thermally conductive silicone composition comprises: The thermally conductive silicone composition was applied between the chip and the nickel-plated aluminum alloy cover plate and cured at 125° C. for more than 2 hours.